Comparative analysis of competitive and specially preparatory exercises of women's arm wrestling - Samsonova, A.V.; Stepanov, V.S.; Zakharov, F.E.; Serov, S.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify effective special-preparatory exercises for female armwrestlers based on the developed criterion for assessing the manifestation of speed-strength abilities. Methods and structure of the study. During the experiment, the electrical activity of the five main muscles of the upper limb of female armwrestlers was studied, followed by statistical processing. The experiment involved nine female athletes (age - 23.3 ± 1.9 years, height - 164.5 ± 1.2 cm, weight - 59.2 ± 2.0 kg) of the entry level, specializing in arm wrestling. After a ten-minute warm-up, the subjects performed competitive exercises using the “hook” and “top” methods and six special preparatory exercises. Results and conclusions. The proposed method makes it possible to single out special preparatory exercises that are most effective for developing the power and strength of a certain muscle group. The most effective exercises for sportswomen performing exercises using “hook” and “top” methods have been determined.